Odpowiedź :
[tex]a) 3\frac{1}{4} + 1\frac{3}{4} = 4\frac{4}{4} = 5\\\\b) 2\frac{3}{4} + \frac{2}{4} = 2\frac{5}{4} = 3\frac{1}{4} \\\\c) 3\frac{2}{10} + 1\frac{7}{10} = 4\frac{9}{10} \\\\d) 4\frac{13}{20} + 12\frac{8}{20} = 16\frac{21}{20} = 17\frac{1}{20} \\\\e) \frac{12}{15} - \frac{7}{15} = \frac{5}{15} = \frac{1}{3} \\\\f) \frac{7}{12} - \frac{3}{12} = \frac{4}{12} = \frac{1}{3} \\\\g) 1 - \frac{3}{7} = \frac{7}{7} - \frac{3}{7} = \frac{4}{7} \\\\[/tex]
[tex]h) 3 - \frac{3}{5} = \frac{15}{5} - \frac{3}{5} = \frac{12}{5} = 2\frac{2}{5} \\\\i) 3\frac{5}{7} - 1 = 2\frac{5}{7} \\\\j) 2\frac{1}{3} - \frac{2}{3} = \frac{7}{3} - \frac{2}{3} = \frac{5}{3} = 1\frac{2}{3\\\\} \\\\k) 3\frac{2}{7} - \frac{5}{7} = \frac{23}{7} - \frac{5}{7} = \frac{18}{7} = 2\frac{4}{7} \\\\l) 2\frac{3}{18} - 1\frac{8}{18} = \frac{39}{18}- \frac{26}{18} = \frac{13}{18} \\\\l)6\frac{12}{20} - 3\frac{19}{20} = 5\frac{32}{20} - 3\frac{19}{20} = 2\frac{13}{20} \\\\[/tex]
[tex]m) 1\frac{2}{5} - \frac{4}{5} + 1\frac{3}{5} = \frac{7}{5} - \frac{4}{5} + \frac{8}{5} = \frac{3}{5} + \frac{8}{5} = \frac{11}{5} = 2\frac{1}{5}[/tex]